(untitled) (Research, Society and Development, 2022)
Vigna unguiculata L. or popularly cowpea as it is known, is one of the main food sources in several countries, especially Brazil. To evaluate the physiological quality of the seeds, it is necessary to use germination and vigor tests. The best known stress-based vigor test is the accelerated aging test, as for the biochemical tests, electrical conductivity and tetrazolium tests stand out. The present work aimed to carry out a literature review on scientific articles published from 2011 to 2021, regarding accelerated aging, electrical conductivity and tetrazolium tests in cowpea seeds. Graphs were made regarding the expressions and keywords: tetrazolium in cowpea seeds; electrical conductivity in cowpea seeds and accelerated aging in cowpea seeds; electrical conductivity in Vigna unguiculata L., accelerated aging in Vigna unguiculata L.; tetrazolium in Vigna unguiculata L. and cowpea in seed vigor tests, considering the Google Scholar, Web of Science and Scielo databases, year of publication and languages ​​(Portuguese, English and Spanish). The Google Scholar database presented a greater number of published articles, as it is a simple and easily accessible platform, unlike the Scielo and Web of Science platforms. The largest number of publications was in 2018, for the accelerated aging, electrical conductivity and tetrazolium tests; with a predominance of the English language. There are several factors that influence the results of vigor tests; not only the genotype, but also the intrinsic conditions of the seeds and the pre- and post-harvest management.